Excitation dependent white and red-NIR emission of a MnII-based complex. Issue 48 (23rd November 2022) - Jabeur, Wiem; Msalmi, Rawia; Korb, Marcus; Hassen, Fredj; Guesmi, Ahlem; Houas, Ammar; Hamadi, Naoufel Ben; Naïli, Houcine
Abstract : The emission from the (AmpH)2 [MnCl4 (Amp)2 ] can be changed from white to red-NIR by excitation wavelengths variation. The red phosphorescence originates from the Mn II octahedral ions, while the NIR-fluorescence is assigned to the [C5 H8 N3 ] + cation. Abstract : Nowadays, organic and organic–inorganic supramolecular crystals are potential candidates for lighting applications. In this work, a new molecular crystal (C5 H8 N3 )2 [MnCl4 (C5 H7 N3 )2 ] abbreviated (AmpH)2 [MnCl4 (Amp)2 ], (C5 H7 N3 = Amp = 2-amino-4-methylpyrimidine), containing octahedral Mn(ii ) complex [MnCl4 (C5 H7 N3 )2 ] 2− and 2-amino-4-methylpyrimidinium cation [C5 H8 N3 ] + has been successfully investigated. The thermal analysis of the synthesized compound shows that it is thermally stable up to 190 °C. The absorption analysis demonstrates an intense absorption band in the UV region with no characteristic absorption in the visible range which makes the material suitable for optoelectronic application. The direct and indirect investigated gap energies are found to be 3.66 and 3.51 eV, respectively, and that proves the semiconducting property of the investigated compound. The solid-state photoluminescence measurements allowed the identification of a broad cold white-light emission under an excitation wavelength of 250 nm. Under an excitation wavelength of 350 nm, the material exhibits an emission centered at around 644 nm assigned to the red phosphorescence emission from the triplet state characteristic of the octahedral Mn II ions. In addition, a broad NIR-emission band is observed between 700 and 900 nm. Hence, the emission from (AmpH)2 [MnCl4 (Amp)2 ] can be varied from white to red-NIR by simple variation of excitation wavelengths. Then the obtained material is suitable for lighting applications such as organic light emitting diodes (OLEDs) and is bio-compatible for bio-sensing and bio-imaging as a heavy atom free material.